2020
DOI: 10.1590/1518-8345.3144.3242
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the questionnaire on threat perception of chronic illnesses in pediatric patients

Abstract: Objective: the objective of the study was to assess the psychometric properties of the Brief Illness Perception Questionnaire in a sample of adolescents with chronic endocrine or pneumological conditions and to analyze the dimensionality and reduce the scale elaborating scales by sex and medical diagnosis. Method: we evaluated 510 patients aged 9-16 years using the Brief Illness Perception Questionnaire and the Hospital Anxiety and Depression Scale. We carried out tests of reliability, construct and criterion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 36 publications
(59 reference statements)
3
24
1
5
Order By: Relevance
“…The analyses performed revealed that the fit of the one-factor model of the BIP-Q5 was better than the two-factor model, showing the validity of the unidimensional model for evaluating the perception of threat from COVID-19. This result coincides with previous studies that have tested the validity and reliability of the BIP-Q5 in an adolescent Spanish population [24], and also with a larger number of studies done with adult populations in other countries using the brief version of the IPQ (BIP-Q) [22]. However, although correlations between residuals in the model enabled us to identify opportunities for improving the instrument, (mainly Item 3 since it was below 0.60 on most of the items on the questionnaire i.e., Items 1, 2, 4, and 5), the test-retest values were optimum, explaining the total for the scale of 43.87 of the variance in perception of the disease.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The analyses performed revealed that the fit of the one-factor model of the BIP-Q5 was better than the two-factor model, showing the validity of the unidimensional model for evaluating the perception of threat from COVID-19. This result coincides with previous studies that have tested the validity and reliability of the BIP-Q5 in an adolescent Spanish population [24], and also with a larger number of studies done with adult populations in other countries using the brief version of the IPQ (BIP-Q) [22]. However, although correlations between residuals in the model enabled us to identify opportunities for improving the instrument, (mainly Item 3 since it was below 0.60 on most of the items on the questionnaire i.e., Items 1, 2, 4, and 5), the test-retest values were optimum, explaining the total for the scale of 43.87 of the variance in perception of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…However, although correlations between residuals in the model enabled us to identify opportunities for improving the instrument, (mainly Item 3 since it was below 0.60 on most of the items on the questionnaire i.e., Items 1, 2, 4, and 5), the test-retest values were optimum, explaining the total for the scale of 43.87 of the variance in perception of the disease. Compared to the study by Valero-Moreno et al [24], internal consistency of the Spanish version adapted to COVID-19 found with the Cronbach's alpha coefficient was acceptable, but somewhat lower.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…But on the other hand, it may strengthen social solidarity, cooperation of people, development of charitable activities and people's organizations, strengthening emotional relations and relationships, strengthening family and the need to increase motivation for work and effort, participation and altruism and altruism and lead to In general, increase participation and social solidarity. [28] In fact, new structures may be incompatible or compatible with mental health. For example, reducing community relationships may increase feelings of loneliness or decrease a person's perception of social support.…”
Section: Discussionmentioning
confidence: 99%